EFFECT OF ADDITION OF CHICKEN EGG SHELL FLOUR IN RATIONS ON THE PERFORMANCE OF 2-6 WEEKS AGED QUAIL - A. W., Sumanti,; Wirapartha, M.; Wijana, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of the addition of purebred chicken eggshell flour in the ration on the performance of quails aged 2-6 weeks and has been conducted for six weeks at Jl. UNUD Lecturer Housing Block F, No. 13, Bukit Jimbaran. The research design used was a completely randomised design (CRD) consisting of 4 treatments and 4 replicates. Each replicate consisted of 4 quails, resulting in 64 two-week-old quails. The four treatments were P0 (100% commercial feed), P1 (100% commercial feed + 4% eggshell meal), P2 (100% commercial feed + 6% eggshell meal), and P3 (100% commercial feed + 8% eggshell meal). The variables observed in this study included feed consumption, drinking water consumption, body weight gain, final weight and ration conversion. The data obtained were analysed using variance analysis, if there were significant differences (P < 0.05) then continued with Duncan's multiple range test. The results showed that the addition of purebred chicken eggshell flour in the ration gave a significant difference (P<0.05) to the increase in body weight gain (PBB), final weight and decreased ration conversion. However, it has not given a significant difference (P>0.05) on the variables of feed consumption and drinking water consumption. Based on the results of the study, it can be concluded that the provision of 4-8% level of purebred chicken eggshell flour in quails has an effect on body weight gain (PBB) and final weight, and reduces ration conversion (FCR) of quails. However, it has not yet influenced quail ration consumption and drinking water.